The Relationship of Stress Levels and Emotional Eating on YARSI University Medical Faculty Students Class of 2020 and The Review According to Islamic Perspective - Salman Shiddiq; Werda Indriarti; Ali Ma'sum (Junior Medical Journal, 2023)
Background: Medical education is almost always associated with high levels of stress. High levels of stress can have a negative impact on cognitive function and learning ability, even though the average study load for medical students is heavier because their class schedules are tighter and their study period is longer. Based on research conducted on first-year medical students at the Faculty of Medicine, Andalas University in 2019, out of a total of 188 respondents, it was found that the majority of respondents had moderate stress levels (48.4%). Stress itself is an unpleasant condition in which a person sees demands beyond the limits of ability. In addition, stress can also change a person's eating behavior. One of them is emotional eating behavior. Emotional eating is an emotional overeating behavior in individuals that arises because of ineffective coping against stress not because of the physiological condition of hunger, but as an effort to improve emotional conditions. The purpose of this study was to determine the relationship between stress levels and emotional eating in YARSI University Medical Faculty students class of 2020 and their views according to Islam.Methods: This research is a quantitative research that is observational analytic with a cross sectional research design. Questionnaires are distributed via google form. This research was conducted on YARSI University Medical Faculty students class of 2020 with a total sample of 138 respondents. Data analysis used the Spearman rank test.Results: Based on the results of statistical tests, there is a relationship between stress levels and emotional eating in YARSI University Medical Faculty students class of 2020. With a p value of 0.003 (p 0.05) and a correlation coefficient of 0.254.Conclusion: There is a relationship between stress levels and emotional eating in YARSI University Medical Faculty students class of 2020, the variable relationship is unidirectional but the relationship is weak.